2014
DOI: 10.4274/tjo.26086
|View full text |Cite
|
Sign up to set email alerts
|

Potec PRK-6000 Otorefraktometre, IOLMaster ve Pentacam ile Ölçülen Keratometri Değerlerinin Tekrarlanabilirliği ve Karşılaştırılması

Abstract: Amaç: Potec PRK-6000 otorefraktometre, IOLMaster ve Pentacam ile ölçülen keratometri değerlerinin tekrarlanabilirliğini ve birbirleriyle olan uyumluluklarını araştırmak. Gereç ve Yöntem: Bu prospektif çalışmada refraksiyon kusuru dışında ek bir oküler patolojisi bulunmayan 55 olgunun 110 gözünde, iki farklı oturumda olmak üzere, bahsedilen üç cihaz ile ardışık ölçümler yapıldı. Her iki oturumda elde edilen düz ve dik keratometri, ortalama keratometri ile korneal astigmatizma değerlerinin tutarlılığı gözlem içi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Although we did not encounter any studies in the literature comparing keratometric analyses of the two devices used in our study, there are various reports using and comparing many different devices and methods in keratometric analysis. 25,26,27 Some of those studies reported that using certain devices as substitutes for one another may not be suitable due to significant differences in keratometric measurements. 26,27 As an explanation, the authors suggested that using different methods to measure keratometry may yield different results.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not encounter any studies in the literature comparing keratometric analyses of the two devices used in our study, there are various reports using and comparing many different devices and methods in keratometric analysis. 25,26,27 Some of those studies reported that using certain devices as substitutes for one another may not be suitable due to significant differences in keratometric measurements. 26,27 As an explanation, the authors suggested that using different methods to measure keratometry may yield different results.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Current devices for measuring posterior corneal analysis use scanning-slit corneal topography (Orbscan; Bausch & Lomb, Inc.), color light-emitting diode topography (Cassini system; i-Optics Corp.; Ophtec), swept-source optical coherence tomography (SS-OCT), and Scheimpflug imaging. [3][4][5][6][7][8][9][10] IOLMaster 700, Anterion (Heidelberg Engineering GmbH), and Eyestar 900 (Haag-Streit AG) devices are based on SS-OCT technology. The Scheimpflug imaging technique is available in many devices such as the Pentacam HR, the Sirius (Costruzione Strumenti Oftalmici), the TMS-5 (Tomey Corp.), and the Galilei (Ziemer Ophthalmic Systems AG).…”
mentioning
confidence: 99%